1987
DOI: 10.1159/000242730
|View full text |Cite
|
Sign up to set email alerts
|

Oral Epidermal Growth Factor Is Trophic for the Stomach in the Neonatal Rat

Abstract: The stomach of the naturally suckled rat pup was shown to grow rapidly during the first 24 h following delivery. Both absolute weight (p < 0.001) and weight in proportion to body weight (p < 0.001) increased. The stomachs of pups fed formula containing epidermal growth factor (EGF) were larger than those of their control littermates (p < 0.05). These data support a role for milk EGF in the regulation of neonatal gut growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…EGF ad ministered orally to suckling rats 3 times daily for 2 days resulted in an increased height of the antral mucosa when high doses were used, whereas the height of the fundic or ileal muco sa was unaffected [12]. Neonatal rats fed a for mula containing EGF displayed an increased weight of the stomach [13], Cultured gastric fundic epithelial cells from adult rabbits were forced into proliferation in a dose-dependent manner by EGF [ 14]. EGF has also previously been proposed to exert a regulatory influence on gastric acid secretion [15,16], It seems as if EGF in the stomach may transiently influence physiological functions such as gastric acid secretion and regeneration of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…EGF ad ministered orally to suckling rats 3 times daily for 2 days resulted in an increased height of the antral mucosa when high doses were used, whereas the height of the fundic or ileal muco sa was unaffected [12]. Neonatal rats fed a for mula containing EGF displayed an increased weight of the stomach [13], Cultured gastric fundic epithelial cells from adult rabbits were forced into proliferation in a dose-dependent manner by EGF [ 14]. EGF has also previously been proposed to exert a regulatory influence on gastric acid secretion [15,16], It seems as if EGF in the stomach may transiently influence physiological functions such as gastric acid secretion and regeneration of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…approximately 30 days during late gestation, in the guinea pig [16][17][18][19] contrasts with the much shorter periods exhibited by altricial species: 4 days in the rat [20] and 5 days in the mouse [21]. These altricial spe cies show further changes in gastrointestinal morphology and physiology during the suck ling period and at weaning [6], Newborn rats fed for 40 h on an artificial formula isocaloric with expressed rat milk had significantly lighter stomachs and intes tines, which contained less DNA and RNA than those fed breast milk [4], It has been suggested that epidermal growth factor in natural milk may account for these differ ences in gastrointestinal growth [22,23], En teral feeding of rats with an artificial formula by gastrostomy from the 5th postnatal day until weaning led to initial deficit in gas trointestinal growth followed by enhanced growth of stomach, small intestine and cae cum [24]. Such findings were also reported when suckling rats were reared on an artifi cial milk from the 12th to 16th postnatal day, though reduction in caloric intake of feeds led to small intestinal growth compara ble with mother-fed rats, together with an inferior rate of body growth [25].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF) is present in the milk of animals of several species (Beardmore and Richards 1983;Moran et al 1983;Jaeger 1987;Schaudies et al 1990) including that of mares (Murray et al 1992). EGF has gastrointestinal trophic effects in neonatal rodents (Berseth 1987;Falconer 1987). EGF has a pronounced effect on keratinocytes in different cell systems (Boonstra ef al.…”
Section: Discussionmentioning
confidence: 99%